Video vs Image: Roles in Fashion Students' Practicum Learning - Siti Zahro; Hany Mustikasari; Didik Nurhadi; Nyan Myau Lyau (Online Learning In Educational Research (OLER), 2025)
In fashion practicums, lecturers generally use learning media for students to help them quickly grasp the material being explained. However, the role of the chosen learning media is often overlooked. Furthermore, this study examined the roles of video tutorials and technical illustrations with images used by fashion students in sewing practicum courses, focusing particularly on the operation of four-thread overlock machines. With a case study and qualitative approach, the researchers explored in-depth data by conducting interviews with fifteen fashion students and observing them operating four-thread overlock machines during the sewing practicum course at the university. Using a thematic analysis, this study found that video tutorials effectively contribute specifically to the learning of fashion students with visual learning styles. On the other hand, technical illustrations with images are effective in facilitating the learning of fashion students with auditory learning styles. In conclusion, lecturers should consider the characteristics of their students when providing learning media, so that those media can be tailored to help achieve learning objectives optimally and facilitate the understanding of media users more efficiently